Development and effectiveness of a normal newborn care simulation education program for nursing students - Hwang, Juhee (Edelweiss Applied Science and Technology, 2025)
This study was conducted to develop and apply simulation-based normal neonatal nursing education and to verify the effects on class satisfaction, learner confidence, and clinical performance ability. The subjects were 65 third-year nursing students in Y City, participating in a single-group pre- and post-test experimental study. Data were collected from March 4 to April 26, 2024, using a self-report questionnaire administered only to students who understood the purpose of the study and provided written consent to participate. Simulation-based normal neonatal nursing education was applied for a total of 8 hours in three stages: preparation for scenario implementation, scenario implementation, and debriefing, with three students in each group. The results of the study showed that there were significant differences in learning satisfaction (t=-7.548, p=0.001), learning confidence (t=-9.163, p=0.001), and clinical performance ability (t=-6.733, p=0.001) before and after simulation-based normal neonatal nursing education. The results of this study confirmed that simulation-based education in the field of pediatric nursing can be an effective teaching and learning method that can supplement observation-based pediatric nursing clinical practice.